A CONTRIBUTION TO THE STUDY OF THE SCANDINAVIAN INFLUENCE IN EASTERN EUROPE OF THE 10TH CENT. AD - Cernecov, Aleksej Vladimirovic (History, Archeology and Ethnography of the Caucasus, 2025)
The article is the continuation of the earlier publication devoted to the interpretation of the decorations on the binding of the aurochs’ drinking-horn from the extremely rich burial of the 10th cent. in the Chernaya Mogila (Ukraine, Chernigov vicinities). The author considers the decoration as an illustration reflecting the central motif of the pagan Scandinavian mythology - “Twilight of the Gods” which is the main part of the first song in the “Elder Edda”. A series of subjects of this narration is identified. The image of the sitting eagle with outspread wings probably points to the mythological character making wind and storm accompanying the catastrophic events. In this case the wind causes the change of the flight of the arrows sent by the anthropomorphic figures (pagan deities or the warriors of their forces – einherjar). An arrow threatens one of the archers himself. The composition placed on the drinking-horn may be associated with the mythical horn Gyallarhorn (one of the gods is trumpeting it at the time of the dramatic events). The motif of plaitings, used in the decorations might  have a sacral meaning in the Scandinavian poetry and applied art. The role of drinking horns in the Scandinavian mythology and pagan rites is discussed. The importance of finds from the Medieval Russian territory including series of pictorial motifs related with the Scandinavian traditions (Odin and his ravens; the dragon stabbed by the sword of Sigurd), the idols of pagan deities, specific amulets and religious symbols are analyzed. The common motifs of the horn decorations and the pagan oaths included into peace treaties of Rus’ and Byzantium (945 and 971) are stressed. The traces of the Norman activities during the early history of Russia does not undervalue the presentation of the historical original nature of the Russian culture since the role of the Scandinavian tradition was sufficiently less important than much more capital cultural influence of Byzantium.
Keywords: Scandinavian influences; East European materials of the 10th cent.